The response of a gravel‐bed river planform configuration to flow variations and bed reworking: a modelling study. Issue 17 (11th May 2015) - Kaless, Gabriel; Mao, Luca; Moretto, Johnny; Picco, Lorenzo; Lenzi, Mario A.
Abstract A 2D depth‐averaged model has been developed for simulating water flow, sediment transport and morphological changes in gravel‐bed rivers. The model was validated with a series of laboratory experiments and then applied to the Nove reach of the Brenta River (Northern Italy) to assess its bed material transport, interpret channel response to a series of intensive flood events (R.I. ≈ 10 years) and provide a possible evolutionary scenario for the medium term. The study reach is 1400 m long with a mean slope of 0.0039 m m−1. High‐resolution digital terrain models were produced combining LiDAR data with colour bathymetry techniques. Extensive field sedimentological surveys were also conducted for surface and subsurface material. Data were uploaded in the model and the passage of two consecutive high intensity floods was simulated. The model was run under several hypotheses of sediment supply: one considering substantial equilibrium between sediment input and transport capacity, and the others reducing the sediment supply. The sediment supply was then calibrated comparing channel morphological changes as observed in the field and calculated by the model. Annual bed material transport was assessed and compared with other techniques. Low‐frequency floods (R.I. ≈ 1.5 years) are expected to produce negligible changes in the channel while high floods may erode banks rather than further incising the channel bed. Location and distribution of erosion and deposition areas within the Nove reach were predicted with acceptable biases stemming from imperfections of the model and the specified initial, boundary and forcing conditions. A medium‐term evolutionary scenario simulation underlined the different response to and impact of a consecutive sequence of floods. Copyright © 2015 John Wiley & Sons, Ltd.